Academic identity in the age of AI higher education and the digital revolution - Nelson, Richard (Emerald points, 2024)
As AI becomes increasingly integrated into the higher education sector, academics are grappling with an identity crisis. Academic Identity in the Age of AI explores the impact of AI on the role of the academic, examines ethical considerations, and envisions the future of higher education academics in the AI era. Delving into the evolving landscape of higher education and its intersection with the rapid developments in generative artificial intelligence, Dr. Richard Nelson presents a comprehensive analysis of these crucial topics and offers insights into navigating the challenges and opportunities presented by the digital transformation of higher education with a key focus on the changing perception of the academic at this time. Chapters explore the historical context of academic identity and the challenges posed by the modern university, emphasising the shifting roles of academics and the complex impact of AI in academia on teaching, assessment and administrative tasks. Featuring compelling case studies illustrating how universities are harnessing the power of AI to innovate in teaching, learning, and research, Academic Identity in the Age of AI offers valuable insights for educators, institution leaders, and policymakers seeking to navigate the ever-changing terrain of AI in education.